Cercarial dermatitis: a systematic follow-up study of human cases with implications for diagnostics - Macháček, Tomáš; Turjanicová, Libuše; Bulantová, Jana; Hrdý, Jiří; Horák, Petr; Mikeš, Libor (Parasitology research, 2018)
Cercarial dermatitis (CD) is an allergic skin disease that rises in consequence of infection by invasive stages (cercariae) of trematodes of the family Schistosomatidae. CD has been considered a re-emerging disease, human cases have been reported from all continents, and tourism-threatening outbreaks occur even in frequented recreational areas. Although the symptoms of CD are generally known, the data on immune response in human patients are sporadic and incomprehensive. In the present study, we attempted to correlate the symptoms, personal history, and time course of CD in human patients with differential cell counts, dynamics of selected cytokines, and dynamics and quality of antibody response. By a systematic follow-up, we obtained a uniquely complex dataset from ten persons accidentally and concurrently infected by the same parasite species in the same locality. The onset of CD was significantly faster, and the symptoms were heavier in participants with a history of CD if compared to naive ones, who, however, also developed some of the symptoms. The repeatedly infected persons had elevated proportion of eosinophils 1 week post exposure (p.e.) and a stronger specific IgG but not IgM response, whereas specific IgE response was not observed. Increased serum levels of IL-4 occurred 1 and 3 week(s) p.e. in all participants. There was high variability in individual immunoblot patterns of IgG response, and no antigen with a universal diagnostic potential was confirmed. The presented analyses suggested that a complex approach can improve the accuracy of the diagnosis of CD, but component data should be interpreted carefully.
Keywords: dospělí; Animals; průzkumy a dotazníky; Female; infekce červy třídy Trematoda; Trematode Infections; imunoglobulin G; interleukin-4; Adult; mladý dospělý; ženské pohlaví; Surveys and Questionnaires; Dermatitis; imunoglobulin M; Ponds; lidé; Schistosomatidae; Immunoglobulin E; následné studie; Immunoglobulin G; Interleukin-4; protilátky protozoální; Disease Outbreaks; Antibodies, Protozoan; Follow-Up Studies; Male; Czech Republic; rybníky; Immunoglobulin M; Young Adult; imunoglobulin E; dermatitida; Česká republika; lidé středního věku; epidemický výskyt choroby; zvířata; mužské pohlaví; Middle Aged; Humans